Slope stabilization / Aina' Wahida Imran - Imran, Aina' Wahida (Universiti Teknologi MARA, Perak, 2019)
Slope instability is a common phenomenon happening around the world. Every problem always have the solution. Slope stabilization is one of the solution to repair a damage slope. A few types of method can be used to stabilize the damaged slope such as rubble wall and stone pitching, soil nailing, gabion wall and rock. Fill and drainage. The purpose of this research is to investigate the method used, which is rubble wall and stone pitching, in stabilizing the damage slope located at Felda Air Tawar 3, Kota Tinggi, Johor. Various method were used to collect and obtain data during this practical training period. At the same time, advantages and disadvantages of the method used were also identified. The cause of the slope damage at Felda Air Ta war 3 is human modification of slope towards parts of the slope to make an access road towards houses down the slope. Necessary excavation and boring were done on the slope surface before constructing the rubble wall, stone pitching and drainage. The construction were on going for 62 days.